2020
DOI: 10.1029/2020sw002473
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and Initial Results of Space Radiation Dosimetry Using the iMESA‐R

Abstract: The integrated Miniaturized Electrostatic Analyzer‐Reflight (iMESA‐R) is a space weather instrument designed to measure plasma density, temperature, and spacecraft charging, along with total ionizing dose and dose rate. A constellation consisting of five nearly identical instruments has been designed and developed to act as science payloads hosted on‐board Department of Defense satellites operating in low‐Earth orbit. To validate the dosimetry component of the iMESA‐R, a radiation test study was performed to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…The results are comparable to the ones obtained in the ISS, with similar differences between measurements and models for the same orbit and duration. Some experiments have been carried out on nanosats such as Timepix [37] or iMERSA-R [38], and on cubesats with experiments such as Lucky7 [39], where active radiation sensors were installed. These missions have demonstrated their ability to detect and accurately determine the flow of protons and electrons.…”
Section: Resultsmentioning
confidence: 99%
“…The results are comparable to the ones obtained in the ISS, with similar differences between measurements and models for the same orbit and duration. Some experiments have been carried out on nanosats such as Timepix [37] or iMERSA-R [38], and on cubesats with experiments such as Lucky7 [39], where active radiation sensors were installed. These missions have demonstrated their ability to detect and accurately determine the flow of protons and electrons.…”
Section: Resultsmentioning
confidence: 99%
“…GPIM (158 kg, ∼715 km altitude, launched in 2019), OTB-1 (∼720 km altitude, launched in 2019), STPSat-4 (∼420 km altitude, launched in 2019), STPSat-5 (115 kg, planned), and STPSat-6 (geosynchronous orbit, planned) have or will have onboard an improved version of the iMESA called integrated miniaturized ESA-reflight (iMESA-R). The iMESA-R was developed to act as simultaneous multi-point sensors to measure plasma density, temperature, spacecraft charging, and total ionizing dose (TID), which was not included in the original iMESA [76]. The design of the iMESA-R used in the five satellites is very similar to ensure consistency across their data.…”
Section: Integrated Miniaturized Esas (Imesas)mentioning
confidence: 99%
“…Besides demonstrating that the sensors were accurate, the ground tests of the iMESA-R also showed that the Al housing encasing the sensor effectively filters out lowenergy electrons and protons, and it only mildly attenuates gamma rays. The initial data from iMESA-R on STPSat-5 is available in [76], and future integration of data from all five iMESA-R sensors is expected to make the measurements more accurate.…”
Section: Integrated Miniaturized Esas (Imesas)mentioning
confidence: 99%
See 2 more Smart Citations